The Deployment Life Study : Methodological Overview and Baseline Sample Description - Terri Tanielian, Benjamin R. Karney (RAND Corporation, 2014)
This report outlines the background, rationale, and methods of the Deployment Life Study; describes the baseline sample included in the study; and provides a context for future analyses using study data. The Deployment Life Study was motivated by a keen interest in military families on the part of U.S. policymakers and researchers. Specifically, recent attention by the U.S. Department of Defense (DoD) has focused on family readiness. When service members and their families are prepared for deployments, they should, in principle, be better equipped than other service members and families to maintain family cohesion and well-being across the deployment cycle. Yet exactly what it means for a military family to be â€œreadyâ€â€”what ready families look like, what resources they use, what can help identify vulnerable familiesâ€”is not well understood. To address these questions, the Deployment Life Study is following 2,724 military families, including families from the Army, Air Force, Navy, and Marine Corps, both active and reserve, over a three-year period. The intent is to capture aspects of these families before deployment, during deployment, and after deployment. Interviews, either by Internet or by phone, occur every four months. Up to three household members are interviewed at each wave of data collectionâ€”the service member, the spouse of the service member, and a study child (if available). This survey design will collect an unprecedented amount of information about what military families look like and how they handle the challenges of military life, and deployments in particular.